“The very environment militates against denial”: Negotiating Place Through Material Culture - Brodie, Ian (Ethnologies, 2005)
In this article the author reflects on the objects brought into his father’s hospice room in the last eight weeks of his life. Objects and their placement were continually renegotiated as he moved through various stages of his disease — greater and lesser pain, appetite, freedom of movement, and lucidity, and shifting timeframes for his imminent passing. The author’s father had no direct control over the presence or absence of objects, and little control over their placement, so that the room became a site of polite contestation among the various parties helping him in his final days.